PENGARUH HIPERTENSI TERHADAP KEJADIAN STROKE: SUATU KAJIAN LITERATUR SISTEMATIS TAHUN 2020–2025 - Ribka Sagala (Journal of Innovation Research and Knowledge, 2025)
Hypertension is a major risk factor for cardiovascular diseases, including stroke. The increasing incidence of stroke worldwide, particularly in developing countries, is often associated with the high prevalence of uncontrolled hypertension. Objective: This study aims to analyze the impact of hypertension on stroke incidence based on scientific evidence from studies published between 2020 and 2025. Methods: This research adopts a Systematic Literature Review (SLR) approach following the PRISMA guidelines. Literature was retrieved from PubMed, ScienceDirect, and BMC databases using the keywords: "hypertension", "stroke", "risk", and "incidence". The inclusion criteria were observational or interventional studies that examined the relationship between hypertension and stroke, published in English between 2020 and 2025. A total of 15 articles were included for analysis. Results: The reviewed studies indicated that hypertension significantly increases the risk of both ischemic and hemorrhagic stroke. Contributing factors include the duration of hypertension, blood pressure variability, and poor hypertension control. Antihypertensive interventions have been shown to reduce the risk of recurrent stroke. Conclusion: There is a strong relationship between hypertension and stroke. Optimal blood pressure management through promotive and preventive interventions is essential in reducing stroke risk.